Practices of trade digitalization in Ukraine and worldwide (Economics and region, 2025)
The transformation of trade through digital technologies has become one of the defining features of the global economic landscape. In the context of increasing complexity of trade interactions, geopolitical tensions, and the growing role of technological platforms, the modernization of trade systems is no longer a matter of competitive advantage, but a prerequisite for resilience and long-term development. The present study investigates the diversity of digitalization practices in trade across countries with a particular focus on the Ukrainian experience. It analyzes global trends in trade digitalization, such as integrated logistics platforms, digital customs, e-invoicing systems, CRM solutions, and digital marketing strategies, and compares them with current transformations observed in Ukraine. The aim of the article is to identify effective tools, strategic approaches, and institutional mechanisms that facilitate the development of digital trade ecosystems. The study proposes a classification of digital tools used in trade based on functionality, scale, and integration level, providing a detailed analysis of their implementation in Ukraine. It explores the role of public initiatives, private technological solutions, and cross-sectoral cooperation in driving digital innovation in commerce. Particular attention is given to the challenges that hinder the full adoption of digital instruments in Ukraine, such as infrastructural fragmentation, regulatory inconsistencies, and limited digital skills among SMEs. Drawing upon both international and domestic sources, the article highlights structural, behavioral, and technological aspects of trade digitalization. It presents a comparative overview of institutional solutions in countries such as the EU, China, the USA, Singapore, and South Korea, emphasizing how these experiences can inform the Ukrainian policy and business agenda. The results indicate that successful digital transformation requires not only technological upgrades but also the formation of integrated digital ecosystems, the development of human capital, and consistent institutional support. The study contributes to the scientific discourse on digital economy and offers practical insights for business strategists, policymakers, and researchers involved in trade modernization.
Keywords: digital trade; e-commerce; marketplaces; CRM systems; digital strategies; digital marketing; logistics platforms